1997
DOI: 10.1159/000190147
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in the Renal Proximal Tubular Cells Induced by lodinated Contrast Media

Abstract: The renal morphologic changes induced by intravenously injected contrast media (CMs) were studied in 40 Wistar rats which had been deprived of water 24 h before the CM injection. In the first part of the investigation, the kidneys were fixed by perfusion for light and electron microscopy 2 h after injection of 3 g iodine/kg of iopamidol, iobitridol or iohexol. Control animals received physiologic saline. In the second part of the study, the fixation was performed 48 h after the injection of the corresponding d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 21 publications
5
41
0
Order By: Relevance
“…4 Pathologic changes of renal tubular cells (e.g., cytoplasmic vacuolar changes, cell death/necrosis, as shown in this study), have been regarded as a characteristic pattern of contrast medium-induced direct tubular injury. 32 Several studies have already shown that contrast medium can directly induce cytotoxic effects or caspase-dependent apoptosis in cultured renal tubular cells 29,33 ; indeed, we also found that Ioversol can activate caspase-3, resulting in apoptosis in cultured LLC-PK1 cells. Furthermore, the preincubation with EPO or asialoEPO can directly inhibit this Ioversol-induced activation of caspase-3 in these cells, with concomitant increments of the phosphorylation of JAK2/STAT5 and expression of HSP70.…”
Section: Discussionsupporting
confidence: 71%
“…4 Pathologic changes of renal tubular cells (e.g., cytoplasmic vacuolar changes, cell death/necrosis, as shown in this study), have been regarded as a characteristic pattern of contrast medium-induced direct tubular injury. 32 Several studies have already shown that contrast medium can directly induce cytotoxic effects or caspase-dependent apoptosis in cultured renal tubular cells 29,33 ; indeed, we also found that Ioversol can activate caspase-3, resulting in apoptosis in cultured LLC-PK1 cells. Furthermore, the preincubation with EPO or asialoEPO can directly inhibit this Ioversol-induced activation of caspase-3 in these cells, with concomitant increments of the phosphorylation of JAK2/STAT5 and expression of HSP70.…”
Section: Discussionsupporting
confidence: 71%
“…1,5 2 -Did the type of contrast -hyperosmolar -used in the study affect the observed results? In Wistar rats, the intravenous injection of contrast agents with similar physicochemical characteristics may cause different intensity and duration changes; 8 however, contrast hyperosmolarity plays a key role in the survival, growth, and proliferation of cultivated human proximal renal tubule epithelial cells. 9 In clinical practice, although the advantages of using low-osmolar and iso-osmolar contrast medium in individuals with a normal GFR have been discussed, these agents have been broadly used to mitigate the adverse effects of osmolarity in renal hemodynamics, particularly in groups at risk of developing CIN.…”
Section: 2mentioning
confidence: 99%
“…Direct tubular toxicity, mediated principally by oxygen free radicals has also been proposed, principally based on studies in vitro (2)(3)(4). In vivo, administration of radiocontrast agents resulted in proximal tubular vacuolar changes and brush border simplification (flattening/loss of microvilli) (5,6). Nevertheless, these tubular anatomic findings seem to represent exposure to radiocontrast rather than true indicators of CIN and lack correlation with kidney dysfunction (7).…”
mentioning
confidence: 99%